Pengaruh Fungsi Badan Pengawas Dan Tingkat Pemahaman Akuntansi Terhadap Kualias Laporan Keuangan (Studi Kasus Koperasi Serba Usaha Sekecamatan Gianyar) - I Dewa Gede Agung Krisna Bayu; Sang Ayu Putu Arie Indraswarawati; I Made Endra Lesmana Putra (Hita Akuntansi dan Keuangan, 2025)
A Financial Report is a means of providing an account of the management of an organization's economic resources in the form of financial information. Local government financial reports should present information that meets the requirements of stakeholders. The objective of this research was to examine the impact of Functions of the Supervisory Board and the Level of Understanding of Accounting on the Quality of Financial Reports in Multi-Business Cooperatives operating in Gianyar District. The population for this study was all 40 MultiBusiness Cooperatives in Gianyar District, and the researcher used purposive sampling method to select 119 participants for the study. The collected data was subjected to multiple linear regression analysis to test the hypotheses. The results of the study indicated that there is a significant and positive relationship between the Functions of the Supervisory Board and the Level of Understanding of Accounting and the Quality of Financial Reports in Multi-Business Cooperatives across the Gianyar District. The results indicate that leaders of Gianyar District Cooperatives should focus on improving their ethical standards to foster employee trust and create role models within the organization. Further research is recommended to expand the research object and refine the questionnaire to ensure that respondents can provide clear and comprehensible answers to questions, which can complement and improve the research